Short Communication: Examining taxa representation in Asian zoos and aquaria using historic records - James Brereton; Shelby Renee Brereton (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Brereton JE, Brereton SR. 2021. Short Communication: Examining taxa representation in Asian zoos and aquaria using historic records. Biodiversitas 22: 2870-2875. According to the World Association of Zoos and Aquariums (WAZA), modern zoological collections should engage in conservation and education-based activities: to do this, the collections must house animals that are interesting to their visitors. There is a plethora of evidence to suggest that zoo visitors and the wider public are more interested in mammals than any other taxa. This ‘mammal bias’ is known to extend into facets of science, such as in reintroduction and zoo research literature. Previous studies on zoo collection planning, however, have identified that globally, zoological collections actually contain more species of bird and fish on average than mammals. At current, there is limited information on the composition of Asian zoological collections. Data on the number of species per taxa (amphibians, birds, fish, invertebrates, mammals, and reptiles) housed at each zoo globally was collected from the International Zoo Yearbook’s ‘Zoos and Aquariums of the World’ from 1960 until 2018. Additional data including the visitor attendance age and size of the collection was recorded. The composition of Asian zoo collection plans was compared against zoos globally, and a longitudinal investigation of Asian Zoo composition was also conducted. Additionally, Poisson regressions were run to determine whether the proportional representation of taxa, year, or visitor attendance were predictors of the numbers of animal species at the collection. Overall, the number of species per taxa significantly differed between Asian collections and the global averages, with Asian collections generally containing greater numbers of invertebrates and fish, and comparatively fewer reptiles. There were similarities in the number of species per taxa over time between Asian collections and zoological collections globally. This study suggests that the influences that affect the species housed in zoos and aquariums more globally are also influencing those in Asian countries.